Pelatihan Pembuatan Brosur Dengan Adobe Photoshop Pada SMA AL Munadi - Joko Bintarto; Yahya Tanjung; M. Fauzi (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2023)
The aim of this community service is to provide participants with the knowledge and skills to be able to create attractive and professional brochures using the Adobe Photoshop application. The method used was SCL (Student Centered Learning) face to face/directly at the Al Munadi High School location for 20 Al Munadi High School students. As a result of the training in making brochures using Adobe Photoshop, the students understood and were able to make brochures as expected.